2016
DOI: 10.15585/mmwr.mm6452a2
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis of Tuberculosis in Three Zoo Elephants and a Human Contact — Oregon, 2013

Abstract: women and women whose pregnancy status was unknown (n = 161), as well as respondents with unreliable dietary recalls (n = 11), yielding 14,728 respondents eligible for analysis. Normal blood pressure was defined as a mean systolic blood pressure <120 mm Hg and mean diastolic blood pressure <80 mm Hg. Hypertension was defined as mean systolic blood pressure ≥140 mm Hg, mean diastolic blood pressure ≥90 mm Hg, or self-reported use of antihypertensive medication. Among persons who did not meet this definition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…Based on positive trunk‐wash cultures or necropsy results, c . 5% of captive Asian elephants in North America are infected with Mycobacterium tuberculosis (Feldman et al ., ), and elephant–human transmission has been reported in multiple cases (Murphree et al ., ; Zlot et al ., ).…”
Section: Pharmacologymentioning
confidence: 97%
See 1 more Smart Citation
“…Based on positive trunk‐wash cultures or necropsy results, c . 5% of captive Asian elephants in North America are infected with Mycobacterium tuberculosis (Feldman et al ., ), and elephant–human transmission has been reported in multiple cases (Murphree et al ., ; Zlot et al ., ).…”
Section: Pharmacologymentioning
confidence: 97%
“…Among captive and working elephants, tuberculosis (TB) is the best-known zoonotic disease and, conversely, humans can also infect elephants with TB (Michalak et al, 1998). Based on positive trunk-wash cultures or necropsy results, c. 5% of captive Asian elephants in North America are infected with Mycobacterium tuberculosis (Feldman et al, 2013), and elephant-human transmission has been reported in multiple cases (Murphree et al, 2011;Zlot et al, 2016).…”
Section: Pharmacologymentioning
confidence: 99%
“…For example, working Asian elephants with an assigned mahout (elephant handler) have an increased risk of TB seropositivity (Yakubu et al., ), but elephants at the African facilities do not have assigned handlers. Close and prolonged contact between humans and elephants, such as spending hours indoors with infected elephants (Zlot et al., ), or cleaning barns and aerosolization during pressure washing (M. Miller & Olea‐Popelka, ) have been implicated in human cases of TB at animal facilities. However, indoor elephant housing does not exist at the facilities in this study, nor are pressure washers in use.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, diseases affecting elephants, including TB, are of particular interest within the TFCA. Elephants in zoological collections around the world have been diagnosed with TB (Lewerin et al, 2005;Mikota et al, 2001;Vogelnest, Hulst, Thompson, Lyashchenko, & Herrin, 2015;Zlot et al, 2015), primarily caused by M. tb or, more rarely, Mycobacterium bovis (Mikota & Maslow, 2011). Infections with zoonotic pathogens transmitted from humans to animals (reverse zoonosis or zooanthroponosis) are more frequently reported in captive animals than their wild counterparts (Epstein & Price, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mtb‐prevalence studies in the living Asian elephant population in the US between 1997 and 2011 have shown an Mtb point prevalence of 5·1%, while it is 0% for African elephants (Feldman et al ., ). However, transmission between elephants as well as from elephants to humans has been documented and these cases fit within the model of known transmission; that is, close prolonged aerosol contact (Murphree et al ., ; Zlot et al ., 2016; Miller et al ., ). There are a few exceptions with unusual scenarios where transmission between elephants and humans appeared to occur as a result of extreme aerosolization of bacteria; in one case when a barn was given a high‐pressure hosing where an untreated known‐to‐be shedding elephant was present and in another case where transmission occurred possibly during a painting demonstration where an elephant used its trunk to spray paint onto a canvas (Murphree et al ., ; Zlot et al ., 2016; Miller et al ., ).…”
Section: Tuberculosis Disease In Elephantsmentioning
confidence: 99%